2021
DOI: 10.3389/fmed.2021.635560
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Clinical Interventions in Critically ill Patient With Coronavirus Disease 2019: A Systematic Review and Meta-Analysis

Abstract: Objective: The aims of this systematic review and meta-analysis were to summarize the current existing evidence on the outcome of critically ill patients with COVID-19 as well as to evaluate the effectiveness of clinical interventions.Data Sources: We searched MEDLINE, the Cochrane library, Web of Science, the China Biology Medicine disc, China National Knowledge Infrastructure, and Wanfang Data from their inception to May 15, 2021. The search strings consisted of various search terms related to the concepts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 54 publications
2
17
0
Order By: Relevance
“…Using a multihospital, single-system cohort of patients with COVID-19 requiring critical care, we found that patients admitted to either general-intensivist-staffed or neurointensivist-staffed ICUs had a similar clinical course and outcome. Our experience across both ICU types is comparable to reported ICU mortality, with national rates ~ 30% (although international rates vary) [ 9 , 10 ].…”
Section: Discussionsupporting
confidence: 70%
“…Using a multihospital, single-system cohort of patients with COVID-19 requiring critical care, we found that patients admitted to either general-intensivist-staffed or neurointensivist-staffed ICUs had a similar clinical course and outcome. Our experience across both ICU types is comparable to reported ICU mortality, with national rates ~ 30% (although international rates vary) [ 9 , 10 ].…”
Section: Discussionsupporting
confidence: 70%
“…Universally, the mortality of critically ill patients with COVID-19 is higher than that of other critically ill patients [53,54]. A main cause for this difference is the characteristics of the SARS-CoV-2 infection, which can rapidly affect other organs including the cardiovascular system [55].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic, initiated by SARS-CoV2 viral infection, illustrates the need for the rapid detection of novel and variant pathogens, as well as specific risk prediction models to identify patients at high risk of severe or fatal disease. Unfortunately, clinical risk models for critically ill patients have been only modestly accurate in predicting outcomes for COVID-19 patients [ 1 ]. Furthermore, similar to septic shock, there is an incomplete understanding of the relative contributions of the pathogen load versus a hyperactive immune response by the host.…”
Section: Introductionmentioning
confidence: 99%